INHtBITION OF SEAFOOD-BORNE BACTERIA IN COOKED MACKEREL RASTRELLIGER KANAGURTA FISH MEAT BY LACTIC ACID BACTERIA - Kannappan, S.; G., Gopalkrishna (Journal of Indian Fisheries Association, 2008)
Antagonistic activity of lactic acid bacteria (LAB) namely Streptococcus faecalis, Pediococcus cerevisiae and Lactobacillus casei was tested against seafood-borne bacteria such as Staphylococcus aureus, Bacillus cereus, Escherichia coli, Clostridium perfringens and Listeriamonocytogenes. Three lactic acid bacteria such as Streptococcus faecalisp Lactobacillus casei and Pediococcus cerevisiae were coated on cooked mackerel meat, individually and in combination against fish-borne bacteria. S. faecalis inhibited C. perfringens in individual coat by 3. 7 log units as compared to control, whereas L. casei did not inhibit C. perfringens. P. cerevisiae inhibited S. aureus by 5 log units. L. casei, inhibited L. monocytogenes by 3.3 log units on the third day ofstorage as compared to control. On the other handS. aureus and B. cereus were inhibited on the third and second day by 4.9 log and 5.2 log units respectively. B. cereus, S. aureus, L. monocytogenes were the most sensitive to all three LAB. C. perfringens was the least inhibitedamong all the seafood-borne bacteria tried. Multiple LAB or LAB strains in combination showed much earlier inhibitory activity on seafood-borne bacteria than single LAB coat.Keywords: lactic Acid Bacteria, Antagonism, Seafood-borne bacteria, C. perfringens, L.